The landscape of biobanks in Poland—characteristics of Polish biobanking units at the beginning of BBMRI.pl organization - Anna Chróścicka (Journal of Translational Medicine, 2021)
Abstract Background Biobanking is an area of scientific activity that is growing in strength and importance. The variety of collections combining biological samples and medical scientific information makes biobanking an indispensable tool in the development of modern medicine. In 2016, Poland, a country with one of the largest populations in Europe, joined the Biobanking and BioMolecular resources Research Infrastructure-European Research Infrastructure Consortium (BBMRI-ERIC) to facilitate access to quality-defined human disease-relevant biological resources. This push led to the development of the Polish Biobanking Network. The purpose of this paper is to present the current state of biobanks in Poland in the context of their location, nature and resources. Methods To obtain information about and overall characteristics of Polish entities dealing with biobanking biological material, the dedicated Information Survey was designed. The survey was prepared in an electronic form and consisted of 53 questions—both open and closed, single and multiple choice—with some questions depending on each other. Sixty-five Polish biobanks/biorepositories participated in the survey. Results Polish biobanks are mostly affiliated with research entities (universities—42% and research institutes—30%). The data collected indicate that a considerable number of Polish biobanks are specialized (33 units), in contrast to population-based biobanks (8 units). These biobanks are mostly focused on collecting samples from oncological (23 biobanks) and rare diseases (12 biobanks). In general, great diversity was found in the material collected. Scientists working in Polish biobanks are very open to scientific cooperation (declared by 60% of units) and sharing their collections with the international scientific environment. In terms of quality issues, most biobanks declared that their quality management system was in the process of implementation (45%) or had already been implemented (23%). Conclusions Although biobanking in Poland is still in its infancy, the results of this study seem promising and may be valuable to the wider biobanking research community. The distribution of biobanks throughout the Polish territory, their connection with scientific and clinical units, and their involvement in research on rare diseases may contribute to an increase in the number of multicenter studies.